Effect of Allicin of Garlic on Production Nitric Oxide of Macrophage to Candida Albicans - M Soltani; M Larypoor; A Akhavan sepahy; M Pirali Hamedani (Institue of Medicinal Plants, ACECR, 2009)
Background: Garlic is an herbal plant having various compounds. one of the most important of which is allicin with antibiotic property. Candida Albicans is opportunistic yeast which in case of immune system dysfunction is considered as a pathogenic agent. Immune mechanisms against this fungus are Macrophages which act with oxidative and non-oxidative fungicide mechanisms. Oxidative mechanism includes active oxygen and nitrogen mediators which are produced by active macrophages and thereby the microorganisms are eliminated. Objective: The aim of this study was to investigate Allicin effects on the increase activites macrophage to product of Nitric Oxide. Methods: It is examined in this study the effect of garlic allicin on macrophages' activity in releasing Nitric oxide against Candida Albicans. Garlic allicin was prepared by the method of chloroformic extract, and then made to react with macrophages from male mouse Balb/c with 2-8 week of age in vitro. Candida Albicans was divided into two groups: with and without allicin. Both cases compared as positive and negative samples, the rate of macrophages' activity was determined through production of Nitric Oxide. Results: After examining the rate of Nitric Oxide produced by macrophages, results showed that allicin as a natural material activates immune system against this fungus, so that macrophages with allicin can produce more Nitric Oxide than the group without allicin. This was obtained by comparing the results from these two groups and the control group. Conclusion: Regarding the important role of Candida Albicans in Candidiasis and applying the preventing agents by this fungus in suppressing the macrophages' activities in producing Nitric Oxide, and also by studying related literatures, we concluded that allicin extracted from garlic can affect greatly on the macrophages' activities in producing Nitric Oxide against agents of Candidiasis disease.